Chronic stability of activated iridium oxide film voltage transients from wireless floating microelectrode arrays - Frederick, Rebecca A.; Shih, Ellen; Towle, Vernon L.; Joshi-Imre, Alexandra; Troyk, Philip R.; Cogan, Stuart F. (Frontiers in Neuroscience, 2022)
Successful monitoring of the condition of stimulation electrodes is critical for maintaining chronic device performance for neural stimulation. As part of pre-clinical safety testing in preparation for a visual prostheses clinical trial, we evaluated the stability of the implantable devices and stimulation electrodes using a combination of current pulsing in saline and in canine visual cortex. Specifically, in saline we monitored the stability and performance of 3000 μm2 geometric surface area activated iridium oxide film (AIROF) electrodes within a wireless floating microelectrode array (WFMA) by measuring the voltage transient (VT) response through reverse telemetry. Eight WFMAs were assessed in vitro for 24 days, where n = 4 were pulsed continuously at 80 μA (16 nC/phase) and n = 4 remained in solution with no applied stimulation. Subsequently, twelve different WFMAs were implanted in visual cortex in n = 3 canine subjects (4 WFMAs each). After a 2-week recovery period, half of the electrodes in each of the twelve devices were pulsed continuously for 24 h at either 20, 40, 63, or 80 μA (200 μs pulse width, 100 Hz). VTs were recorded to track changes in the electrodes at set time intervals in both the saline and in vivo study. The VT response of AIROF electrodes remained stable during pulsing in saline over 24 days. Electrode polarization and driving voltage changed by less than 200 mV on average. The AIROF electrodes also maintained consistent performance, overall, during 24 h of pulsing in vivo. Four of the in vivo WFMA devices showed a change in polarization, access voltage, or driving voltage over time. However, no VT recordings indicated electrode failure, and the same trend was typically seen in both pulsed and unpulsed electrodes within the same device. Overall, accelerated stimulation testing in saline and in vivo indicated that AIROF electrodes in the WFMA were able to consistently deliver up to 16 nC per pulse and would be suitable for chronic clinical use.